Relationship between childhood parentification, adult attachment styles, and addiction: a review - Çetin Demirtaş, Sinem; Yeşiloğlu, Caner; Tamam, Lut (Journal of Dependence, 2025)
Childhood parentification—a role reversal in which children assume caregiving responsibilities for their parents—has emerged as a significant early-life risk factor for adverse mental health outcomes in adulthood. This narrative review synthesizes the literature on the long-term psychological effects of parentification, focusing particularly on adult attachment styles and addiction risk. Drawing from attachment theory, family systems theory, and developmental psychopathology, the paper explores how unmet emotional needs and disrupted caregiving dynamics contribute to insecure attachment patterns, emotion regulation deficits, and the use of maladaptive coping strategies, including substance use and behavioral addictions. Evidence from cross-sectional, longitudinal, and intergenerational studies is presented, highlighting consistent associations between childhood parentification and increased rates of depression, anxiety, personality disorders, and addictive behaviors. Special attention is given to the mediating role of adult attachment insecurity and the intergenerational transmission of caregiving dynamics. Clinical implications include the importance of assessing early family roles in psychotherapy and addiction treatment, with recommendations for attachment-informed interventions. Gaps in the literature are discussed, emphasizing the need for longitudinal research, cultural comparisons, and examination of resilience factors. The review underscores that while parentified children often carry invisible burdens into adulthood, therapeutic insight and targeted interventions may offer pathways to healing and relational growth.